2020
DOI: 10.1080/13880209.2020.1720745
|View full text |Cite
|
Sign up to set email alerts
|

Er Miao San, a traditional Chinese herbal formula, attenuates complete Freund’s adjuvant-induced arthritis in rats by regulating Th17/Treg cells

Abstract: Context: Er Miao San (EMS) is a traditional Chinese medicine composed of Atractylodis Rhizoma and Phellodendri Cortex in a 1:1 weight ratio. EMS has been used to treat rheumatism in China for many years. Objective: To evaluate the anti-arthritic activity of EMS extract on adjuvant-induced arthritis (AA) in Sprague-Dawley rats and to clarify its mechanisms of action. Materials and methods: EMS (0.75, 1.5 and 3 g/kg, once daily) was orally administered from day 18 after immunization to day 31. The effects of EMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 24 publications
0
16
0
Order By: Relevance
“…In the current study, the compound decoction added more 2 kinds of Chinese herbs on the basis of the above formula including Cortex phellodendri and Rhizoma Atractylodis to strengthen its power of dispelling wind, removing dampness, and clearing heat. Previous studies have proved that the combination of Cortex phellodendri and Rhizoma Atractylodis (Er-Miao-San) exhibits antiarthritic activity via regulating the balance of cytokines [ 32 , 33 ]. The major finding of our study was that Shentong Zhuyu Decoction can inhibit the inflammatory response, migration, and invasion and promote apoptosis of rheumatoid arthritis fibroblast-like synoviocytes via the MAPK p38/PPAR γ /CTGF pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, the compound decoction added more 2 kinds of Chinese herbs on the basis of the above formula including Cortex phellodendri and Rhizoma Atractylodis to strengthen its power of dispelling wind, removing dampness, and clearing heat. Previous studies have proved that the combination of Cortex phellodendri and Rhizoma Atractylodis (Er-Miao-San) exhibits antiarthritic activity via regulating the balance of cytokines [ 32 , 33 ]. The major finding of our study was that Shentong Zhuyu Decoction can inhibit the inflammatory response, migration, and invasion and promote apoptosis of rheumatoid arthritis fibroblast-like synoviocytes via the MAPK p38/PPAR γ /CTGF pathway.…”
Section: Discussionmentioning
confidence: 99%
“…RA is the most prevalent chronic and long-term autoimmune inflammatory disease (Wang et al, 2017a;Li et al, 2019a;Saleem et al, 2020;Zhu et al, 2020). Although there are many anti-RA drugs in clinic, such as immunosuppressants, biological agents, DMARDs, steroidal drugs, and NSAIDs, most of them are associated with long-term adverse effects and costs (Li et al, 2019b;Dai et al, 2020;Zhu et al, 2020). In addition, the CFA-induced arthritis (AIA) model and the collagen-induced arthritis model are two typical preclinical experimental animal models of RA, and the former is a classic, easy-to-measure, short duration, reliable and reproducible test animal model, which is extensively used for the preclinical evaluation of anti-RA drugs since its pathological and morphological characteristics were similar to those of human RA Pan et al, 2017;Voon et al, 2017;Zhang et al, 2019;Saleem et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the serum levels of these inflammatory mediators were determined by enzyme-linked immunosorbent assay (ELISA) kits (Lin et al, 2013;Wang et al, 2017a). Currently, immunosuppressants, biological agents and disease-modifying anti-rheumatic drugs (DMARDs), and steroidal and non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used for the treatment of RA, but most of them display long-term adverse effects, toxicity and comorbidities (Dai et al, 2020;Li et al, 2019a, Li et al, 2019bRui et al, 2019). As a result of this, exploring effective and safe anti-RA drug candidates from natural products, especially traditional folk medicines, could be a momentous breakthrough.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that EMS water extract has a therapeutic effect on AA rats, significantly reducing the pathological index and paw swelling in rats with arthritis [12]. In order to further study the effective antiarthritis parts of EMS, these were extracted using different organic solvents, such as dichloromethane, ethyl acetate, chloroform, and petroleum ether.…”
Section: Discussionmentioning
confidence: 99%